Health-related quality of life in long-term differentiated thyroid cancer survivors: A cross-sectional Tunisian-based study - Missaoui, Abdel Mouhaymen; Hamza, Fatma; Maaloul, Mohamed; Charfi, Hana; Ghrissi, Wiem; Abid, Mohamed; Guermazi, Fadhel (Frontiers in Endocrinology, 2022)
Background and Aim: The incidence of differentiated thyroid cancer (DTC) has risen dramatically worldwide. Despite an excellent prognosis, the growing DTC survivors' community often features poor health-related quality of life (HRQoL), which challenges long-term DTC care, particularly in developing Southern Mediterranean and African countries. We aimed to assess the HRQoL and to investigate its determinants in disease-free Tunisian DTC survivors. Methods: We conducted a three-month cross-sectional study that included 266 patients diagnosed with DTC. We assessed the HRQoL in eligible participants using the short form–36 health survey, in comparison with 76 healthy controls. Results: The 86 eligible DTC survivors were predominantly female (89.5%) with an average age of 44.3±12.5 years. Physical-functioning (PF), role-physical (RP), and pain domains were substantially altered compared to the reference population. Age was negatively associated with PF, RP, role-emotional (RE), and social functioning (SF). Tumor size and lymph node metastases affected general health and PF, respectively. The cancer-free survival duration was positively correlated with mental health (MH). Poor neck scar healing and persistent post-operative hypoparathyroidism significantly deteriorate MH. Pain perception was positively correlated with the radioactive iodine cumulative dose. Subclinical hyperthyroidism significantly reduced PF and RP scores. TSH suppression was negatively and strongly correlated with MH and SF scores. Conclusion: HRQoL is substantially reduced in DTC survivors compared to the normative Tunisian population. These results could be extrapolated to similar individuals in other South Mediterranean and African countries. The development of coordinated multidisciplinary aftercare interventions in this region is warranted to preserve HRQoL in DTC survivors.